Organisational ecology in tourism: A regional labour market perspective - Anne-Mette Hjalager (European Regional Science Association (ERSA), 1998)
Tourism is often claimed to be a major employment creator and a viable path to development in rural areas. Covering the period 1980-1994, Danish data of the overall growth in the number of enterprises and jobs support the optimism forwarded, except for the most densely populated areas. The paper goes into greater depth of the dynamics of regional tourism development by investigating organisational birth, survival and mortality among restaurants and accommodation facilities. The study of the organisational ecology unveils a considerable turbulence, e.g. high numbers of entries as well as exits. Stability tends to correlate positively with agglomeration. In some - but not all - respects, a higher stability among the enterprises in urban areas results in qualitatively different and more permanent types of employment.
Keywords: 330